Answer:
![\displaystyle x \approx 37.4^\circ](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%20%5Capprox%2037.4%5E%5Ccirc)
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtraction Property of Equality<u>
</u>
<u>Trigonometry</u>
- [Right Triangles Only] SOHCAHTOA
- [Right Triangles Only] cosθ = adjacent over hypotenuse<u>
</u>
Step-by-step explanation:
<u>Step 1: Define</u>
Angle θ = <em>x</em>
Adjacent Leg = 5.8
Hypotenuse = 7.3
<u>Step 2: Solve for </u><em><u>x</u></em>
- Substitute in variables [Cosine]:
![\displaystyle cosx^\circ = \frac{5.8}{7.3}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20cosx%5E%5Ccirc%20%3D%20%5Cfrac%7B5.8%7D%7B7.3%7D)
- [Fraction] Divide:
![\displaystyle cosx^\circ = 0.794521](https://tex.z-dn.net/?f=%5Cdisplaystyle%20cosx%5E%5Ccirc%20%3D%200.794521)
- [Equality Property] Trig inverse:
![\displaystyle x^\circ = cos^{-1}(0.794521)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%5E%5Ccirc%20%3D%20cos%5E%7B-1%7D%280.794521%29)
- Evaluate trig inverse:
![\displaystyle x = 37.39^\circ](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%20%3D%2037.39%5E%5Ccirc)
- Round:
![\displaystyle x \approx 37.4^\circ](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%20%5Capprox%2037.4%5E%5Ccirc)
Solve for f:(i - 47/12) + f = 18
(i - 47/12) + f = f + (-47/12 + i):
f + (-47/12 + i) = 18
Subtract -47/12 + i from both sides:
Answer: f = 263/12 - i
When you have something like this, all you need to do is substitute the values, the last is for what value of x
For the first one;
((x^2+1)+(x-2))(2)
(x^2+x-1)(2)
(2)^2+(2)-1
4+2-1
5
For the second one;
((x^2+1)-(x-2))(3)
(x^2-x+3)(3)
(3)^2-(3)+3
9-3+3
9
For the last one;
3(x^2+1)(7)+2(x-2)(3)
3((7)^2+7)+2((3)-2)
3(49+7)+2(3-2)
3(56)+2(1)
168+2
170
The solution is x=3/4
How can we solve given equation?
First, we will solve like terms. Then shift constant to other side and keep x on the same side to get the value of x.
We can solve given equation as shown below:
5/2-3x-5+4x=-7/4
(5-10)/2+x=-7/4
-5/2+x=-7/4
x=5/2-7/4
x= (10-7)/4
x=3/4
Hence, the solution is x=3/4.
Learn more about Linear equations here:
brainly.com/question/43297
#SPJ4
Answer:
49 and 58
Step-by-step explanation:
pls brainliest